MENINGKATKAN HASIL BELAJAR MATERI PENGURANGAN BILANGAN CACAH DENGAN TEKNIK MEMINJAM MELALUI MEDIA KANTONG BILANGAN SISWA KELAS III SD MUHAMMADIYAH 1 LIMBOTO KABUPATEN GORONTALO - Patma Ahmad; Abd Hamid Isa; Yulanti S. Mooduto (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
The purpose of this study was to improve learning outcomes of whole number subtraction material with borrowing technique through number bag media for grade III students of Muhammadiyah 1 Limboto Elementary School, Gorontalo Regency. The type of research used was classroom action research with 23 grade III students as research subjects. This study used techniques, namely interviews, observations, tests, and documentation. Data analysis techniques were teacher activities, student activities, and learning outcomes of whole number subtraction material with borrowing technique. The research was conducted in two cycles, cycle I three meetings and cycle II three meetings with four stages, namely: planning stage, implementation stage, observation stage and reflection stage. The results of the study showed that in the initial observation there were 3 students with a percentage of 13% who had a passing grade and 20 students or 87% with an incomplete grade. Furthermore, in cycle I there was an increase to 14 students with a percentage of 61% with a passing grade. In cycle II, as many as 21 students had a passing grade with a percentage of 91%. The results achieved in cycle II have exceeded the established performance indicators. Thus, it can be concluded that through the number bag media, it can improve the learning outcomes of the material on reducing whole numbers with the borrowing technique of grade II students of Muhammadiyah 1 Limboto Elementary School, Gorontalo Regency.